Hubungan Depresi dan Pilihan Aplikasi Smartphone dengan Kecanduan Smartphone Pada Siswa SMA - Ferianti Ferianti; Sunawan Sunawan (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2021)
Advances in information and communication technology offer a sophisticated smartphone that has the potential to lead to addiction. Previous studies found smartphone addiction is motivated by the presence of psychological factors such as depression experienced by a person. In addition, previous studies also found a determining factor that is the magnitude of smartphone addiction different depends on the types of smartphone applications selected. Therefore, current research aims to identify the relationship between depression and the choice of smartphone apps with smartphone addiction in students. Current research is quantitative research methods. The participants of this study were 307 students. The instruments used in the study consisted of a depression scale, smartphone addiction scale, and smartphone app selection questionnaire. The data was analyzed using product-moment correlation. The data analysis revealed a positive correlation coefficient value of 0.468 with a significance of 0.000 (p>0.05), meaning there was a positive association between depression and smartphone application choices with smartphone addiction in students. Thus, it can be concluded that the higher the level of depression experienced, the higher the level of smartphone addiction of students. Then, the choice of smartphone apps displayed a different impact on the level of smartphone addiction. Game applications have fewer percentages of voters compared to social media applications. However, game applications have a bigger influence on students' smartphone addiction.